Adiposity, mediating biomarkers and risk of colon cancer in the European prospective investigation into cancer and nutrition study. Issue 3 (5th August 2013) - Aleksandrova, Krasimira; Drogan, Dagmar; Boeing, Heiner; Jenab, Mazda; Bas Bueno‐de‐Mesquita, H.; Jansen, Eugene; van, Fränzel J.B.; Rinaldi, Sabina; Fedirko, Veronika; Romieu, Isabelle; Kaaks, Rudolf; Riboli, Elio; et al.
<x xml:space="preserve">Abstract</x> Adiposity is a risk factor for colon cancer, but underlying mechanisms are not well understood. We evaluated the extent to which 11 biomarkers with inflammatory and metabolic actions mediate the association of adiposity measures, waist circumference (WC) and body mass index (BMI), with colon cancer in men and women. We analyzed data from a prospective nested case–control study among 662 incident colon cancer cases matched within risk sets to 662 controls. Relative risks (RRs) and 95% confidence intervals (CIs) were calculated using conditional logistic regression. The percent effect change and corresponding CIs were estimated after adjusting for biomarkers shown to be associated with colon cancer risk. After multivariable adjustment, WC was associated with colon cancer risk in men (top vs. bottom tertile RR 1.68, 95% CI 1.06–2.65; ptrend = 0.02) and in women (RR 1.67, 95% CI 1.09–2.56; ptrend = 0.03). BMI was associated with risk only in men. The association of WC with colon cancer was accounted mostly for by three biomarkers, high‐density lipoprotein cholesterol, non‐high‐molecular‐weight adiponectin and soluble leptin receptor, which in combination explained 46% (95% CI 37–57%) of the association in men and 50% (95% CI 40–65%) of the association in women. Similar results were observed for the associations with BMI in men. These data suggest that alterations in levels of these metabolic biomarkers may represent a primary mechanism of action in the relation of adiposity with colon cancer. Further studies are warranted to determine whether altering their concentrations may reduce colon cancer risk.